Performance parameters of protocol AOMDV under random obstacle mobility model - Liliana, Enciso; Luis, Mengual (International Journal of Engineering and Technology, 2019)
A Mobile Ad Hoc Network (MANET) is a collection of mobile nodes that are dynamically self-configured, with no physical infrastructure nor centralized administration. In this article, we discuss which of the routing strategies for MANETs: proactive, reactive or hybrid, has a better performance. For the measurement, we have established thirty-six simulation for emergency scenarios in an urban area. This involved, in addition to quality of service (QoS) parameters defined, the calculation of the node densities and the usage of a mobility model needed to validate the results. These must determine which routing protocol has better QoS under the Random Obstacle Mobility Model. The simulator using was NS2 version 2.35.Â Â